2018
DOI: 10.5152/tjar.2018.98058
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Efficacy of Dexmedetomidine and Fentanyl as Adjuvants to Ropivacaine in Ultrasound-Guided Supraclavicular Brachial Plexus Block

Abstract: Objective: Supraclavicular brachial plexus block is preferable to general anaesthesia in upper limb surgeries. Various adjuvants have been added to improve the quality of the block and prolong postoperative analgesia. The aim of the present study was to compare the onset and duration of sensory and motor blockade with the quality of perioperative analgesia and postoperative complications provided by dexmedetomidine and fentanyl as adjuvants to ropivacaine under ultrasound (USG) guidance in supraclavicular bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
(24 reference statements)
4
11
0
Order By: Relevance
“…A significant prolongation in duration of sensory and motor block was observed in group D when compared to group F. Present study results also showed that the duration of analgesia is prolonged in group D than group F. These results were comparable to the studies done by P.S. Dharmarao et al 22 , Mohamed et al 23 where they observed that dexmedetomidine prolongs the duration of anesthesia and analgesia when compared to fentanyl. Hemodynamic parameters were similar in all groups.…”
Section: Resultssupporting
confidence: 89%
“…A significant prolongation in duration of sensory and motor block was observed in group D when compared to group F. Present study results also showed that the duration of analgesia is prolonged in group D than group F. These results were comparable to the studies done by P.S. Dharmarao et al 22 , Mohamed et al 23 where they observed that dexmedetomidine prolongs the duration of anesthesia and analgesia when compared to fentanyl. Hemodynamic parameters were similar in all groups.…”
Section: Resultssupporting
confidence: 89%
“…Dexmedetomidine when added to ropivacaine prolongs the duration of motor blockade as compared to clonidine and fentanyl. Similar results were noted in other studies [9,10,11].…”
Section: Discussionsupporting
confidence: 93%
“…Vallem Balasubramanyam [10], concluded that that dexmedetomidine 1 mcg/kg as an adjuvant result early onset of motor blockade, prolonged duration of motor blockade and with better quality of block as compared to clonidine 1 mcg/kg when added to ropivacaine in supraclavicular brachial plexus block. Dharmarao P and Holyachi R [11], noted that Dexmedetomidine prolongs the duration of motor block as compared to fentanyl but the onset of motor blockade was not statistically significant among the two study groups. While Nyla Farooq [8], noted that fentanyl 1mcg/kg when added to 0.75% ropivacaine was most efficacious than dexem 1mcg/kg when added to 0.75% ropivacaine in onset of motor block having 20 mins for fentanyl group and 30 min in dexem group.…”
Section: Discussionmentioning
confidence: 89%
“…[10]. Dexmedetomidine is an α2 adrenoceptor agonist highly special and selective, with α2: α1 selectivity binding ratio [11,12]. Our results in agreement with, Schnabel et al [13].…”
Section: Discussionsupporting
confidence: 90%